OXYGEN ISOTOPE ANALYSIS OF PHOSPHATES: A COMPARISON OF TECHNIQUES FOR ANALYSIS OF AG3PO4 - Vennemann T.W.; Fricke H.C.; Blake R.E.; O'Neil J.R.; Colman A. (My University, 2002)
A comparison has been made of oxygen isotope analyses of natural and synthetic phosphates using three methods in current use and Ag3PO4 as the analyte. Of these methods, conventional fluorination using BrF5 provides the most precise and accurate measurements and these analyses serve as the basis for comparison. Fluorination liberates 100% of the oxygen in Ag3PO4 and the isotopic composition of this oxygen can be readily normalized to accepted oxygen isotope ratios of international reference standards. The widely used method of high-temperature reaction with graphite in isolated silica tubes is also precise but requires calibration for scale compression resulting from a combination of factors including incomplete extraction of oxygen, reaction temperature, possible oxygen exchange with the silica tube and/or differences in the grain size of the graphite used. The recently developed method based on high-temperature carbon reduction and continuous flow mass spectrometric analysis of CO is relatively fast, requires little sample and provides 100% yields for oxygen. At the present time, this method is less precise than the other methods examined and requires calibration against standards on a run to run basis.Five phosphate reference standards with δ18O values ranging from -5.2%% to 34.0%% were prepared and packaged for distribution to active workers in the field. Analyses of these standards will allow normalization and calibration of results obtained using any available method of oxygen isotope analysis of phosphate.
Keywords: OXYGEN; ISOTOPES; PHOSPHATES; ANALYSIS; METHOD